Implementasi MES Pada Testing Dan Pick & Place Station Berbasis Iot Dan Aplikasi Mobile - Yuliadi Erdani; Adhitya Sumardi Sunarya; Jody Jovantio (AI Society & STMIK Indonesia, 2024)
Monitoring and controlling the industrial production process in Indonesia is still mostly done manually, this causes errors and delays in collecting information and the delivery process. Manufacturing execution system (MES) is one type of production management software that is useful for capturing data automatically and in real time. Manufacturing execution system can be implemented with internet technology that can be accessed remotely. Internet of Things (IoT) is a concept that is connected to devices as an internet-based communication medium. MES and IoT can be connected with Flutter which will later become a media interface that will be displayed on mobile applications. The use of mobile-based information systems is intended to optimize data processing and information results.